Assessment of maternal Doppler parameters of ophthalmic artery in fetuses with growth restriction in the third trimester of pregnancy: A case–control study. Issue 9 (4th June 2015) - Melo, Nayana Alves De Brito; Araujo Júnior, Edward; Helfer, Talita Micheletti; Caetano, Ana Carolina Rabachini; Zamarian, Ana Cristina Perez; Moron, Antonio Fernandes; Diniz, Angélica Lemos Debs; Nardozza, Luciano Marcondes Machado
Abstract Aim The aim of this study was to assess the Doppler parameters of the ophthalmic artery of pregnant women carrying fetuses with growth restriction (FGR) compared with normal fetuses. Material and Methods A prospective cross‐sectional study was conducted with 120 pregnant women (60 FGR and 60 normal fetuses) between 32 and 40 weeks of gestation. FGR diagnosis was based on an estimated fetal weight below the 10th percentile of the Hadlock curve. Ophthalmic artery Doppler images were obtained with a linear transducer, with color Doppler examination of the region medial to the optic nerve. The following indices were obtained: pulsatility index, resistance index, peak systolic velocity, second peak velocity (P2), end diastolic velocity, and P2 / peak systolic velocity ratio. The Mann–Whitney U‐test and Student's t‐test were used to compare the groups with regard to quantitative variables, and the χ2‐test was used for categorical variables. Results Pulsatility index and resistance index were significantly lower in pregnant women with FGR than in those with normal fetuses, with P < 0.001 in both indices. P2 and end diastolic velocity were significantly higher in pregnant women with FGR than in those with normal fetuses (P = 0.002 and P = 0.004, respectively). The P2 / peak systolic velocity ratio was significantly higher in the FGR group than in the control group (P < 0.001). In FGR subgroups, with (17 fetuses) and without (43 fetuses) uterine artery Doppler abnormalities, no significant changes were observed between the groups. Conclusion In the third trimester of pregnancy, we observed significant differences in the ophthalmic artery Doppler parameters of pregnant women with FGR compared with those with normal fetuses.